Identifying the big question in international business research - Peng, Mike W (Journal of International Business Studies, 2004)
Buckley (2002) argues that the international business (IB) research agenda may be running out of steam, because no big research question has currently been identified. Buckley also asks whether the field needs a big question, and if so challenges IB scholars to discover it. Buckley and Ghauri (2004) elaborate on the third question of globalization discussed in Buckley (2002) as a possible candidate for the big question. In response, this article is written to take up Buckley's challenge and also to comment on Buckley and Ghauri's more recent work. I agree that IB needs a big question, the pursuit of which can serve to unite and energize scholars, make scientific progress, and enhance the status and prestige of the field. Toward that end, I argue that ‘What determines the international success and failure of firms?’ has always served as a fundamental research question, which has permeated IB research in the past and present and is likely to propel its progress in the future. Therefore, I am of the opinion that the IB research agenda is not likely to run out of steam, because focusing on this question will leverage IB's comparative advantage and keep the field engaged in generating exciting and disciplined theories and findings in the 21st century.